The effect of perceived service quality on customer emotions, customer satisfaction and customer loyalty: A PLS-SEM approach towards a luxury hotel in Bangkok, Thailand - Suwanamas, Chayuth; Trimetsoontorn, Jirasek; Fongsuwan, Wanno (My University, 2015)
Creating emotionally touching experiences using tangible and intangible cues is critical to attract, satisfy and retain customers. However, support for the effect of service quality on customer emotions, satisfaction and loyalty in Thai hotels is scant. Therefore, this study aims to propose and test a model that describes the relationships between perceived service quality, customer emotions, satisfaction and loyalty in a five-star hotel setting in Bangkok, Thailand. A self-selection sampling technique was used to select the sample by sending the questionnaires to the guests who stayed at the hotel, out of which 425 guests returned the completed questionnaires. Partial least squares (PLS)-based structural equation modelling (SEM) was used to analyse the collected data, assess the model and test the hypotheses. All the hypotheses were proven and our findings confirm that perceived service quality impacts customer emotions and customer satisfaction significantly and all of these jointly influence customer loyalty.
Keywords: Customer loyalty; Customer satisfaction; Hotels; Intangible service quality; Perceived service quality; Tangible service quality